Reef site and habitat influence effectiveness of Acropora palmata restoration and its microbiome in the Florida Keys - Stephanie M. Rosales; Benjamin D. Young; Allan J. Bright; Enrique Montes; Jia-Zhong Zhang; Nikki Traylor-Knowles; Dana E. Williams (Communications Earth & Environment)
Abstract The success of coral restoration for the critically endangered Acropora palmata is understudied. Here, we examined how habitat and coral microbiomes influenced survivorship in four genets of A. palmata outplanted in three reefs. A. palmata microbiomes were correlated to reef and habitat and minimally to coral genet. Carysfort Reef exhibited the lowest survivorship which correlated to lower current velocity and a higher relative abundance of Rhodobacterales in A. palmata. Higher survivorship was present at Pickles Reef which correlated to the highest current velocity, and at North Dry Rocks with the shallowest outplant depth. Habitat factors driven by time of year such as higher levels of nitrate, nitrite, and temperature also correlated with a relative increase in a putative pathogen, Alteromonadales, and a decrease in an uncharacterized core bacteria. We suggest outplanting at sites with high currents, lower depths, and at lower concentrations of nitrate/nitrite to increase A. palmata survivorship.